MENGINTEGRASIKAN PENDEKATAN ILMIAH YANG BERPUSAT PADA MALL (MOBILE ASSISTED LANGUAGE LEARNING) DALAM PEMBELAJARAN MENULIS BAHASA INGGRIS - Irma Savitri Sadikin; Oktian Fajar Nugroho; Muhamad Bahrul Ulum (STKIP Siliwangi, 2024)
Writing has often been considered a challenging skill to master. The purpose of this research is to investigate the effect of a scientific approach based on Mobile Assisted Language Learning (MALL) on enhancing students' descriptive writing abilities. This investigation employed classroom action research with twenty-four ninth-grade junior high school students in West Jakarta as participants. The research was conducted in two cycles, utilizing observation, interviews, and a series of writing tests to collect data. The results indicated that students' writing improved as a consequence of the use of a scientific approach based on MALL. By engaging them in a number of practices at each meeting, working with websites and applications, and seeking feedback from both students and teachers, MALL tended to enhance students' writing abilities. Implementing a scientific approach supported by MALL has shown potential in helping learners enhance their ideas in writing. They demonstrated their ability to create lengthy paragraphs supplemented with relevant details. Students boosted their vocabulary learning by using digital dictionaries and watching videos. Regular feedback from peers and teachers were crucial in helping students understand the significance of punctuation and spelling accuracy in their written work. Therefore, it is advised to conduct additional scholarly research to examine the effectiveness of the scientific approach based on MALL, covering not just writing skills but also extending to reading, speaking, or listening skills.